2015
DOI: 10.1007/s00784-015-1496-2
|View full text |Cite
|
Sign up to set email alerts
|

TiF4 improves microtensile bond strength to dentin when using an adhesive system regardless of primer/bond application timing and method

Abstract: Pretreatment with TiF(4) increased bond strength in a conventional two-step adhesive system to dentin, regardless of the primer/adhesive application method and the timing of dentin pretreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Studies have observed that the incorporation of particles into the hybrid layer may lead to an increase in energy occurring during failure, resulting in fracture propagation into substrates (in dentin or resin) other than the bond interface [35]. Tranquilin et al [11] showed that the use of 2.5% TiF 4 as dentin pretreatment led to an increase in the frequency of cohesive failures in dentin when the convention three-step adhesive system was used, shown by means of the microtensile bond strength test. Similarly, Devabhaktuni and Manjunath [10] observed higher frequency of cohesive and mixed failures in resin when using the shear test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have observed that the incorporation of particles into the hybrid layer may lead to an increase in energy occurring during failure, resulting in fracture propagation into substrates (in dentin or resin) other than the bond interface [35]. Tranquilin et al [11] showed that the use of 2.5% TiF 4 as dentin pretreatment led to an increase in the frequency of cohesive failures in dentin when the convention three-step adhesive system was used, shown by means of the microtensile bond strength test. Similarly, Devabhaktuni and Manjunath [10] observed higher frequency of cohesive and mixed failures in resin when using the shear test.…”
Section: Discussionmentioning
confidence: 99%
“…Dündar et al [9] verified that pretreatment with an aqueous solution of 2.5% titanium tetrafluoride (TiF 4 ) interfered in the bond strength of adhesive cements to dentin. For etchand-rinse adhesive systems, Devabhaktuni and Manjunath [10] observed that the application of a 4% aqueous solution of TiF 4 before or after acid etching when using a 3-step adhesive system had no influence on the bond to dentin, whereas Tranquilin et al [11] verified that the use of pretreatment with 2.5% TiF 4 promoted higher bond strength values of a two-step adhesive system to dentin. In addition, a hybrid layer micromorphology with the formation of more numerous and larger diameter tags was obtained, showing the favorable effects of using this pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Tranquilin et al 43 verificaram a inclusão do TiF 4 , no pré tratamento dentinário a fim de aumentar a resistência adesiva nos sistemas adesivos de dois passos. Como resultados obtiveram um aumento na resistência adesiva na inclusão desse composto.…”
Section: Revisão Da Literaturaunclassified
“…The titanium tetrafluoride (TiF 4 ) is another solution that has been studied. The TiF 4 is an intermediately strong acid (pH about 1.5), capable to promote adhesion between the titanium and the oxygen atom from phosphate groups, forming a vitreous layer, resistant to acid and alkaline solutions 18–25 . Considering that SARCs are composed by acidic components, including phosphoric acid groups, the application of titanium tetrafluoride molecules into the hybrid layer could be relevant for the bonding mechanism.…”
Section: Introductionmentioning
confidence: 99%